Indian Handicrafts: A Sustainable future of Utilitarian Consumer Goods - Choudhary, Akanksha; Mishra, Poonam (Ushus Journal of Business Management, 2022)
Utilitarian products are those which are designed to be useful rather than attractive. Handmade products are, thus, one among the wonders of Indian artisans, which are both useful and attractive at the same time. World-renowned Indian handicrafts are imported by several countries, which is highly supporting Indian art and culture. This is a source of livelihood for more than half of the unskilled labours and artisans of the Handicraft Industry. But with high-quality décor, luxurious items being exported to foreign lands, middleman income and trade fairs are sucking up most of the profits. Indian artisans and handicraft workers are therefore left with little income in hand except for the very famous art workers of big businessmen. This is one of the major problems which can be solved by encouraging the supply of handicrafts and domestic consumer demand. Since Indian consumers have been evolving through manufactured products, globalization, industrialization, etc. they are producing harmful effects on the environment and socio-economic conditions. Hence, it is very alarming for the handicraft sector to be able to protect its art and small business during an economic crisis. To address the small businesses and art of poor craftworkers this study intends to focus on the utilitarian aspect of handicrafts as being the sustainable alternative. The research broadly focusses on the socio-economic conditions of rural artisans and the environmental benefits of handicrafts by assessing the demand of domestic consumers and their perspectives. Based on primary data collected through the survey method, the study finds that domestic consumers are aware of the sustainable alternative handicrafts have to offer, while the utilitarian aspect has a vague response when it comes to purchasing handicrafts. However, demand for handicrafts is high because of their utilitarian aspect only. The study applied multiple regression analysis to analyse the results and conclude with suggestions based on qualitative research analysis to support rural handicraft artisans and small businesses. The study initiates a broad scope of research in consumer behaviour towards handicrafts in India as a sustainable alternative to mass production. This is one of the ways of supporting the cultural art forms as well as replenishing sustainability in the three major directions, which are economic, environmental & societal. Based on the empirical findings of this study, it concludes with the suggestions of co-existence with culture and sustainable development in India.